ANALYSIS OF RAW MATERIAL INVENTORY RECORDING AND VALUATION METHODS BASED ON SAK EMKM FOR BUSINESS CONTINUITY AT THE SUPER SUMBER SARI TOFU AND TEMPE FACTORY IN GORONTALO CITY - Widya Astuti; A. Harun Blongkod; Ayu Rakhma Wuryandini (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the methods of recording and valuing raw material inventories based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and their relation to business continuity at the Super Sumber Sari Tofu and Tempe Factory in Gorontalo City. This research employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that the Super Sumber Sari Tofu and Tempe Factory in Gorontalo City has not implemented inventory recording in accordance with SAK EMKM. The business has not determined an inventory valuation method and does not calculate inventory values at the end of the accounting period. This condition causes the financial statements prepared to be unable to accurately reflect the business condition, particularly in determining inventory values and cost of goods sold. However, in terms of inventory expense recognition, the factory has applied it by recognizing damaged raw material inventories as expenses in the period incurred. This is due to the fact that raw materials are purchased from regular suppliers, making damaged materials non-returnable. The main factor contributing to the absence of inventory recording in accordance with SAK EMKM is the limited accounting knowledge of the owner and business managers, who are more focused on production and sales activities. Therefore, the implementation of inventory recording in accordance with SAK EMKM is expected to assist the business in preparing better financial statements and supporting business continuity.